2014
DOI: 10.11604/pamj.2014.17.227.2695
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction and associated factors among diabetic men attending diabetic clinic at Muhimbili National Hospital in Dar-es-Salaam, Tanzania

Abstract: IntroductionThere has been an increase in the prevalence of erectile dysfunction (ED) in the general population especially among Diabetic patients. This seems to be neglected problem in low-income countries. This study aims at establishing the prevalence of ED and associated risk factors in diabetic patients attended at Diabetic Clinic at Muhimbili National Hospital.MethodsA cross-sectional hospital based study was conducted among 312 diabetic patients attending diabetic clinic at Muhimbili National Hospital b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 66 publications
16
64
1
Order By: Relevance
“…Recruitment strategy about ED patients is also a significant covariate. Epidemiological studies have shown that ED could be caused by psychogenic and physiologic factors [29]. The studies included in this meta-analysis consisted of ED patients, whereas some did not.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment strategy about ED patients is also a significant covariate. Epidemiological studies have shown that ED could be caused by psychogenic and physiologic factors [29]. The studies included in this meta-analysis consisted of ED patients, whereas some did not.…”
Section: Discussionmentioning
confidence: 99%
“…Overall information regarding the prevalence was obtained from various countries in Africa. Three of the studies were from Nigeria [42][43][44], three from Ethiopia [11,45,46], two from Zimbabwe [41,47] ,two from South Africa [40,48], one each from Guinea [49], Benin [18], Morocco [50], Egypt [24], Senegal [51], Kenya [52], Ivory coast [53], Tanzania [54], Uganda [55],and Ghana [20].…”
Section: Baseline Characteristic Of the Included Studiesmentioning
confidence: 99%
“…Erectile dysfunction has been identified to be a major problem amongst diabetes mellitus patients (Mutagaywa et al 2014). Erectile dysfunction has been defined as the inability to achieve and maintain an erection which is sufficient to permit satisfactory sexual intercourse (Mutagaywa et al 2014) (Hackett 2009). The causes of erectile dysfunction are classified into organic or psychogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Organic causes of sexual dysfunction are drug induced, traumatic/post-surgical, vascular, endocrine induced and neurological. Whilst psychogenic causes include relationship problems, performance anxiety and depression (Mutagaywa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation